Does Religious Affiliation Protect People's Well‐Being? Evidence from the Great Recession after Correcting for Selection Effects. Issue 2 (11th December 2020) - Makridis, Christos A.; Johnson, Byron; Koenig, Harold G.
Abstract: This paper investigates the effect of religious affiliation on individual well‐being. Using Gallup's U.S. Daily Poll between 2008 and 2017, we find that those who are engaged in their local church and view their faith as important to their lives have not only higher levels of subjective well‐being, but also acyclical levels. We show that the acyclicality of subjective well‐being among Christians is not driven by selection effects or the presence of greater social capital, but rather a sense of purpose over the business cycle independent of financial circumstances.